Measuring the efficiency of presentation skills in business and educational contexts in Hungary - Zita Komár; Veronika Pelle (Netcom)
The study reports on a research that aims to conceptualise the notion of successful and efficient communicator and presentation in business contexts. Following a literature review on empirical studies and research conducted in business settings, the paper introduces the design of the complex methodology of the examination as well as the challenges and new perspectives of the research. It also reports on the shift in the scope of examination from business to educational contexts, comparing employers’ and future employees’ expectations about vital communication and presentation skills. The theoretical and methodological frameworks are completed by a Hungarian case study conducted among university students and a final outlook to the current state of communication skills development in (higher) education with lessons to consider.